Analisis Penilaian Postur Kerja Karyawan Dengan Menggunakan Metode NBM, Rula dan Reba - Ridwan Darussalam (CV. Publikasi Indonesia, 2022)
In the industrial world, good working environment conditions are a must that must be obtained by every worker. Special attention needs to be paid to working conditions including work postures as they relate to occupational health and safety. The problem that exists at Indomaret Kemang Pratama Raya is that there are complaints experienced by workers related to work postures in loading and unloading activities that can affect other work activities. The research method used NBM (Nordic Body Map), RULA (Rapid Upper Limb Assessment), and REBA (Rapid Entire Body Assessment). This study aims to determine the complaints experienced by workers and the risks associated with work postures in loading and unloading activities and provide suggestions for improvements that need to be made to improve the work postures of workers. The number of samples in this study was 5 employees. Based on the results obtained from 5 employees that the spell results are 18 where the number indicates a high risk at work, the RULA results are 10 and REBA 11, and the results of Rula and Reba also show the same results as the spell, meaning a large number of risks. With these problems, it can be concluded that the method used in the study can be used to provide suggestions for improvements in the form of trolleys that can help employees and reduce the level of risk that exists.